Analysis of the cooperative learning methodology applied for improving the development of speaking skill in students at 10th Grade of Basic General Education "J" in Unidad Educativa "Miguel Angel León Pontòn", in the city of Riobamba, Chimborazo Province during the Academic Year 2019-2020. - Fatima Marisol, Saigua Llamuca (2020)
This research deals with the cooperative learning method that aims to organize activities within the classroom to turn them into a social an academic learning experience that helps to develop linguistic skills in the second language by having a relationship with it, obtaining a degree necessary comprehension with the second language, and speaking fluently, the cooperative method being a set of pedagogical teaching procedures based on teamwork and small mixed and heterogeneous groups where students manage the coordinated way among themselves to solve tasks academic and deepen your own learning , the objective of this research work is to analyze how the cooperative learning methodology is applied to improve the development of the ability to speak in the tenth grade of Basic General Education "J" in the Educational Unit "in the academic period 2019-20202020. In which the qualitative scientific method was applied because it corresponds to the sciences of education, with a descriptive, bibliographic, and field approach. The main problem found in the research was that the students are not used to working team and have problems communicating orally due to the lack of practice of the language. In addition, other factors were identified that also stand out, such as the lack of confidence to speak. in front of their classmates, afraid of being teased and judged when they make a mistake. These factors have influenced the personality of the students to avoid speaking in English. In addition, limiting the time they receive language classes delays the learning process of oral skills.